Implementation of Employee Retention Strategy to Increase Employee Loyalty at Atalla Bakery Store - Anisah , Azizah; Maidalena , Maidalena; Nasution , Muhammad Syukri Albani (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
This study aims to identify policies and factors that influence employee retention and their impact on employee loyalty at Atalla Bakery. Maintaining employees as a company's main asset is crucial to ensuring organizational productivity and stability. This study uses a qualitative approach with descriptive methods , with data collection techniques through interviews, observations, and documentation. The results show that employee retention strategies at Atalla Bakery include providing incentives, performance-based bonuses, flexibility in working, and career development opportunities. Although a supportive work environment and adequate benefits have been implemented, several challenges remain, such as high workloads at certain times and limitations in training programs. The conclusion of this study emphasizes the importance of developing a more comprehensive retention strategy to increase employee loyalty sustainably.